Effects of multiple mating in males on female reproduction: evidence for sperm depletion in Trinidadian guppies - van der Walle,Tess Makenna (2025)
According to sexual selection theory, males should benefit more from mating with multiple partners than females do as male investment into offspring production is typically lower. However, male reproductive success might not increase indefinitely with an increasing number of female mating partners. Male ejaculates are limited, and so mating with multiple females over a short period of time may cause a decrease in the quantity and quality of sperm, which might, in turn, affect female reproductive success. Here, we investigated the effect of multiple mating in males on female reproductive success in a laboratory population of Trinidadian guppies (Poecilia reticulata), a species known for its polygamous mating system. We created mating groups of two different sizes: 16 males had weekly one-on-one mating opportunities with four females and 14 males with seven females, respectively. Females (n = 170) were immature virgins when first mated, and we recorded their age at first parturition, the number of offspring in the first litter, and their probability of reproductive failure until the age of 160 days. We found that a larger mating group size caused a 13% delay in female age at first parturition and a 32% increase in litter size. While the former is due to either sperm depletion or male mating fatigue, the latter is likely a consequence of the females’ larger size when giving birth at an older age. Only 5.3% of females did not reproduce, and so statistical power for detecting an effect of mating group size on the probability of reproductive failure was insufficient. Accordingly, even though twice as many females failed to reproduce in the larger mating groups (3.6% vs. 1.8%), this difference was not significant. Our findings suggest that, even in a highly polygamous species, male reproductive performance might be limited, potentially rendering the strength of sexual selection more similar between males and females than conventionally assumed.